Pemanfaatan Limbah Plastik Bekas Gelas Kemasan Untuk Meningkatkan Kekuatan Campuran Beton Sebagai Bahan Rigid Pavement - Calosa, Evanthe; Putra, Sasana; Noorhidana, Vera Agustriana; Karami, Muhammad (Universitas Lampung, 2022)
Concrete is the main material of rigid pavement that can withstand compressive strength and weak to tensile strength. Flexural tensile strength on rigid pavement itself is a benchmark in concrete pavement. To increase the value of the flexural tensile strength can be done by adding fiber to the concrete mixture. The purpose of this study was to determine the effect of the addition of plastic waste from plastic packaging made of polypropylene on the compressive strength and flexural tensile strength of concrete.In this study, the addition of used plastic waste pieces from packaged glass used fractional volumes of 0%, 0.1%, 0.3%, 0.5%, and 0.7% of the volume of concrete mixture. The samples for this study were a cylinder with a diameter of 15 cm and a height of 30 cm for the compressive strength test and a beam measuring 15 x 15 x 60 cm for the flexural tensile strength test. The test was carried out after the concrete had been 28 days old. The result of this research is the compressive strength decreased along with the amount escalation of the fiber to the concrete mixture. The flexural tensile strength maximum occur of the addition of plastic fibers at 2% volume fraction increased by 23,75% compared to flexural tensile strength of normal concrete. As a result of adding plastic fibers to the concrete mixture, it also decreased the workability of the concrete mixture